The Influence of Microfinance, Interest in Entrepreneurship and Business Location on the Development of Micro, Small and Medium Enterprises - Ahmad Syarief Iskandar; Hendra Safri; Ummul Hasanah Sahar (Jurnal Ad'ministrare, 2021)
the development of MSMEs in Palopo City. The method used in this study is quantitative; data collection was carried out using a questionnaire with 200 customers of microfinance Bank Syariah Mandiri Sub-Branch Office Palopo City. Samples were taken using the Slovin formula with 66.66 rounded up to 67 people. The data analysis technique used is multiple linear regression. The results show that: 1) Islamic bank microfinance variable (X1) partially affects the development of MSMEs. 2) The variable of interest in entrepreneurship (X2) has no partial effect on the development of MSMEs. 3) The business location variable (X3) partially affects the development of MSMEs. 4) Variables of microfinance (X1), interest in entrepreneurship (X2), and business location (X3) simultaneously affect the development of MSMEs. The results of the partial research / T-test, the variable of Islamic bank microfinance (X1) Tcount > T table, ie 2,296 > 1,998 with a significant level of 0.025 < 0.05. The results of the partial test / T-test of the entrepreneurial interest variable (X2) Thitunng < T table, namely -0.712 < 1.998 with a significance level of 0.479 > 0.05. The results of the partial test / T-test of the business location variable (X3) Tcount > T table ie 3,627 > 1,998 with a significant level of 0.001 < 0.05. Simultaneous test (F test) obtained variable results (X1), (X2), and (X3) have a simultaneous effect on the MSME development variable (Y) because Fcount > Ftable is obtained, which is 10.548 > 2.76 with a significance value of 0.000 < 0.05. The implications of the results of this study suggest that BSM KCP Palopo City further improves services to customers accompanied by the provision of technical assistance and open access to microfinance for MSME actors down to the smallest sector to achieve more equitable welfare. As well as increasing socialization about Islamic banks, especially about Islamic microfinance. The implications of the results of this study suggest that BSM KCP Palopo City further improves services to customers accompanied by the provision of technical assistance and open access to microfinance for MSME actors down to the smallest sector to achieve more equitable welfare. As well as increasing socialization about Islamic banks, especially about Islamic microfinance. The implications of the results of this study suggest that BSM KCP Palopo City further improves services to customers accompanied by the provision of technical assistance and open access to microfinance for MSME actors down to the smallest sector to achieve more equitable welfare. As well as increasing socialization about Islamic banks, especially about Islamic microfinance.Acharya, A. S., Prakash, A., Saxena, P., & Nigam, A. (2013). Sampling: Why and how of it. Indian Journal of Medical Specialties, 4(2), 330–333.Afifah, R. Z., & Setiawan, A. H. (2012). Analisis Bantuan Modal dan Kredit Bagi Kelompok Pelaku Usaha Mikro oleh Dinas Koperasi dan UMKM Kota Semarang (Studi Kasus: KPUM Di Kelurahan Pekunden, Kecamatan Semarang Tengah) [PhD Thesis]. Fakultas Ekonomika dan Bisnis.Ahmadun, A. (2015). Usaha Mikro, Kecil Dan Menengah (Umkm) Sebagai Basis Ekonomi Kerakyatan. Jurnal Administrasi Dan Manajemen, 5(1).Anggraini, R. R. (2013). Persepsi orangtua terhadap anak berkebutuhan khusus (deskriptif kuantitatif di SDLB N. 20 Nan Balimo Kota Solok). Jurnal Penelitian Pendidikan Khusus, 2(1).Brilian, A. (2013). Prosedur Pembiayaan Talang Haji IB Hasanah pada PT. Bank BNI Syariah Kantor Cabang Surakarta.Etikan, I., & Bala, K. (2017). Sampling and sampling methods. Biometrics & Biostatistics International Journal, 5(6), 00149.Fitriati, R. (2015). Menguak Daya Saing UMKM Industri Kreatif: Sebuah Riset Tindakan Berbasis Soft Systems Methodology. Yayasan Pustaka Obor Indonesia.Fuadi, A. O., & Mangoting, Y. (2013). Pengaruh kualitas pelayanan petugas pajak, sanksi perpajakan dan biaya kepatuhan pajak terhadap kepatuhan wajib pajak UMKM. Tax & Accounting Review, 1(1), 18.Ilyas, R. (2015). Konsep pembiayaan Dalam perbankan syari’ah. Jurnal Penelitian, 9(1).Kishan, R. P., & Opiela, T. P. (2006). Bank capital and loan asymmetry in the transmission of monetary policy. Journal of Banking & Finance, 30(1), 259–285.Ma’ruf, A., & Wihastuti, L. (2008). Pertumbuhan ekonomi indonesia: Determinan dan prospeknya. Jurnal Ekonomi & Studi Pembangunan, 9(1), 44–55.Neely, A. (2008). Exploring the financial consequences of the servitization of manufacturing. Operations Management Research, 1(2), 103–118.Rejeki, F. Y. S. (2013). Akad Pembiayaan Murabahah dan Praktiknya Pada PT Bank Syariah Mandiri Cabang Manado. Lex Privatum, 1(2).Rukajat, A. (2018). Pendekatan penelitian kuantitatif: Quantitative research approach. Deepublish.Santos, J. A., & Winton, A. (2019). Bank capital, borrower power, and loan rates. The Review of Financial Studies, 32(11), 4501–4541.Santoso, G. (2015). Determinan koefisien respon laba. Parsimonia-Jurnal Ekonomi Dan Bisnis, 2(2), 69–85.Sugiarti, H., & Megawarni, A. (2012). Konsistensi Koefisien Determinasi sebagai Ukuran Kesesuaian Model pada Regresi Robust the Consistency of Coefficient of Determination to Fitting Model Through Robust Regression. Jurnal Matematika Sains Dan Teknologi, 13(2), 65–72.Sulistyo, S. (2010). Pengembangan USAha Kecil dan Menengah dengan Basis Ekonomi Kerakyatan di Kabupaten Malang. Jurnal Ekonomi Modernisasi, 6(1), 58–73.Tambunan, T. (2012). UMKM Indonesia. BUKU DOSEN-2014.Trihudiyatmanto, M. (2019). Pengembangan Kompetensi Kewirausahaan Untuk Meningkatkan Keunggulan Bersaing UMKM (Studi Empirik Pada UMKM Pande Besi di Wonosobo). Journal of Economic, Management, Accounting and Technology (JEMATech), 2(1), 22–32.